Maternal Risk Factors and Perinatal Outcome of Fetal Growth Restriction - Rajbhandary, Sanyukta; Maskey, Suvana (Journal of Nepal Health Research Council, 2024)
Background: Worldwide, Fetal growth restriction is a leading cause of stillbirth, neonatal mortality, and morbidity. Several maternal factors influence fetal growth and increases the risk of fetal growth restriction. Our study aimed to determine the risk factors and perinatal outcome of fetal growth restriction at Tribhuvan University teaching hospital, Maharajgunj, Kathmandu. Methods: A prospective study was conducted in the department of Obstetrics and Gynecology at Tribhuvan University teaching hospital. A total of 140 Pregnant women at > 28 weeks period of gestation clinically diagnosed as FGR and fulfilling the inclusion criteria were enrolled in this study. The data was analyzed using SPSS 23. The association between various risk factors and FGR was studied using the binary logistic regression. Results: Among the 140 FGR fetuses, 27.9 % (39) belonged to the <10th percentile (Mild Fetal growth restriction) and 72.1%(101) belonged to<5th percentile (Severe Fetal growth restriction). Maternal age more than 35 years was found to be statistically significant as a risk factor in the severe Fetal growth restriction group. Among the maternal co-morbidities, hypertensive disorder of pregnancy was found to be the most common co-morbidity followed by heart disease and thyroid disorders. The Fetal growth restriction neonates requiring neonatal intensive care unit (NICU) stay was 42 (30%) and the median neonatal intensive care unit stay was 4 days. The fetal morbidities associated with fetal growth restriction were prematurity,respiratory distress syndrome(RDS), sepsis, meconium aspiration syndrome(MAS) and neonatal jaundice (NNJ). Among the 140 FGR babies, 138 were live born and there were 2 neonatal deaths (NND). Conclusions: In our study ,advanced maternal age is found to be a significant risk factor for Fetal growth restriction and gestational hypertension is the most common comorbidity associated with Fetal growth restriction. Therefore, identification of such women, their regular antenatal checkups, fetal surveillance and timely intervention are crucial for better perinatal outcome. Keywords: Fetal growth restriction, fetal outcome, risk factors.